2018
DOI: 10.1111/cote.12380
|View full text |Cite
|
Sign up to set email alerts
|

A sultone‐based reversible dark red‐yellow conversion thermochromic colorant with adjustable switching temperature

Abstract: A reversible, adjustable thermochromic colorant with bichromatic conversion from dark red (cool state) to yellow (heat state) was prepared using bromocresol purple (BCP) as colour former. The thermochromic behaviour of this colorant was investigated during the heating‐cooling cycle, including the colour depth, colour difference and switching temperature. The mechanism of thermochromic colorant switching between dark red and yellow originated from the transformation of the conjugated structures of BCP, which wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Further evidence of the CPR structure in our binary thermochromic system comes from FTIR analysis ( Figure S4 of Supporting Information). FTIR measurements indicated that the binary system of CPR-TD (10 mol%) at both hot liquid (70 °C) or cool solid (25 °C) showed similar peaks attributed to the sulfone group at 1345 and 1191 cm −1 which indicates a ring-closed CPR structure 21 at both temperatures and different colours. After treatment with base however, peaks at 1180 and 1630 cm -1 due to the benzene sulphonate and p-quinoid groups respectively appear 53,54 which are consistent with the ring opened structure of CPR.…”
Section: Please Do Not Adjust Marginsmentioning
confidence: 95%
See 1 more Smart Citation
“…Further evidence of the CPR structure in our binary thermochromic system comes from FTIR analysis ( Figure S4 of Supporting Information). FTIR measurements indicated that the binary system of CPR-TD (10 mol%) at both hot liquid (70 °C) or cool solid (25 °C) showed similar peaks attributed to the sulfone group at 1345 and 1191 cm −1 which indicates a ring-closed CPR structure 21 at both temperatures and different colours. After treatment with base however, peaks at 1180 and 1630 cm -1 due to the benzene sulphonate and p-quinoid groups respectively appear 53,54 which are consistent with the ring opened structure of CPR.…”
Section: Please Do Not Adjust Marginsmentioning
confidence: 95%
“…20 Recently, they have been used to fabricate thermochromic systems, for example, one sulfonephthalein dye (bromocresol purple) was used as a colour former in a three-component thermochromic system, in which stearic acid was the developer and long-chain Please do not adjust margins Please do not adjust margins alcohols were described as solvents with the reversible ringopening mechanism similar to that of the leuco dye system. 21 π-π stacking, a non-covalent interaction between molecules, has been reported to be the source of reversible thermochromism in conjugated polymers 22,23 and crystals [24][25][26] . It has also been used to explain colour changing phenomenon of aggregachromic dyes with highly conjugated planar structures 9,27 , such as triphenylenes 28 and perylene bisimides 29 , which form dimers or other agglomerates in solution with an increase in dye concentration.…”
Section: Introductionmentioning
confidence: 99%